Characteristic of herd immunity among the population of Stavropol region amid the COVID-19 epidemic - A. Yu. Popova; E. B. Ezhlova; A. A. Melnikova; V. S. Smirnov; L. V. Lyalina; A. V. Ermakov; N. I. Solomashchenko; I. V. Kovalchuk; E. A. Vasilenko; E. N. Romanenko; A. V. Zvoliborskaya; A. V. Ryabykh; et al. (Журнал инфектологии, 2021)
Introduction. The first pandemic in the 21st century, caused by the pathogenic representative of the coronavirus SARS-CoV-2, began in the Chinese city of Wuhan, where the first outbreak of coronavirus pneumonia was recorded in December 2019. The disease spread so quickly around the world that already on February 11, 2020, WHO was forced to declare a pandemic of the “coronavirus disease 2019” COVID-19. The first case of COVID-19 in the Stavropol Territory was registered on March 20, 2020, and three weeks later, starting from the 15th week of the year, a steady increase in the incidence began, which lasted until the 52nd week. During the study period, the incidence increased from 21.1 to 28.3 per hundred thousand of the population. Growth 1.3 times.Purpose: to determine the dynamics of population immunity among the population of the Stavropol Territory in 2020-2021. during the period of an epidemic increase in the incidence of COVID-19. Materials and methods. The SARS-CoV-2 study was carried out according to a unified methodology within the framework of the program for assessing the population immunity of the population of the Russian Federation, developed by Rospotrebnadzor with the participation of the St. Pasteur. In total, 2688 people were examined, divided into 7 age groups. In the examined individuals, the level of specific IgG to the SARS-CoV-2 nucleocapsid was determined by the enzyme immunoassay.Results. The level of seroprevalence among residents of the Stavropol Territory was 9.8%. The largest proportion of seropositive individuals was found in the age groups 1-6 and 7-13 years old (19.2% and 19.7%, respectively). Seroprevalence had no gender differences and ranged from 9.3% to 10.8%. When assessing the distribution of the proportion of seropositive persons in different geographic territories of the region, it was found that the maximum proportion was found in the Kochubeevsky district (23.1%), the minimum in Kislovodsk (7.7%). Among convalescents, the content of specific antibodies to SARS-CoV-2 was noted in 73.3%, which is 7.8 times higher than the average population level. When conducting seromonitoring in the 2nd half of 2020, a 10-fold increase in seroprevalence was recorded, accompanied by a decrease in incidence from the 5th week of 2021. Among asymptomatic volunteers in whom SARS-CoV-2 RNA was detected by the polymerase chain reaction, antibody titers to viruses were found in 78.6%, which corresponds to the seroprevalence of convalescents. The proportion of seropositive persons among those who have come into contact with COVID-19 patients was 16.4%, (1.8 times higher than the average for the population). Out of 262 seroprevalent volunteers, the asymptomatic form of SARS-CoV-2 was detected in 92% of the examined, which indicates a significant role of the number of asymptomatic forms of infection in the epidemic process of COVID-19.Conclusion. The results of assessing the population immunity of the population of the Stavropol Territory indicate that it has not yet reached the threshold level at which a decrease in the intensity of the COVID-19 epidemic process can be expected.